MEDICAL PROFESSIONALS AS EFFECTIVE COMMUNICATORS - DEDDY MULYANA (Communication, 2015)
This paper discusses some issues related to the rationale for studying health communication,especially the reasons why medical practitioners must master therapeutic communicationwhich is often culture-bound. It is argued that in this era of globalization medical professionalsneed to have communication skills in order to treat patients from various cultures effectively.These communication skills, characterized by empathy, intimacy and intercultural competencewill make medical professionals more successful in their careers.